Ethical Approval and Being a Virtuous Social Work Researcher. The Experience of Multi-site Research in UK Health and Social Care: An Approved Mental Health Professional Case Study. Issue 2 (2nd April 2020) - Stone, Kevin; Vicary, Sarah; Scott, Charlotte; Buckland, Rosie
ABSTRACT: Seeking ethical approval and conducting research in an ethical manner are necessary components of research with human participants. Using the experiences of four individual studies undertaken separately into the same role, that of the Approved Mental Health Professional (AMHP), this article critically examines the challenges for multi-site research in health and social care settings. Issues arising are discussed: these are systemic and procedural, or barriers encountered using the integrated approach of the National Research Ethics Service. We discuss the lessons learned and argue that seeking ethical approval in multi-site research is currently a static construct involving the satisfying of what are in effect closed systemic and procedural requirements. We suggest that being a virtuous social work researcher, which we explore in the context of contemporary debates in social sciences, should instead afford open-ended integrity whereby the 'permission' granted is constantly revisited by the researcher or, in other words, that the integrated approach should allow being a virtuous researcher. We suggest that this cyclical activity has particular resonance for those researchers who are, simultaneously, health and social care practitioners. The article adds to the literature on ethics, conduct and integrity in health and social care.